1997
DOI: 10.1086/303717
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet Emission‐line Ratios of Cataclysmic Variables

Abstract: We present a statistical analysis of the ultraviolet emission lines of cataclysmic variables (CVs) based on ≈ 430 ultraviolet spectra of 20 sources extracted from the International Ultraviolet Explorer Uniform Low Dispersion Archive. These spectra are used to measure the emission line fluxes of N V, Si IV, C IV, and He II and to construct diagnostic flux ratio diagrams. We investigate the flux ratio parameter space populated by individual CVs and by various CV subclasses (e.g., AM Her stars, DQ Her stars, dwar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
45
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 33 publications
6
45
0
Order By: Relevance
“…In this respect it is worth pointing out that, in contrast to the large number of UV (mostly IUE) and far-UV (mostly FUSE) studies for other classes of CVs (see, for example, Verbunt & Wade 1984;La Dous 1991;Mauche et al 1997;Araujo-Betancor et al 2005;Long 2006; Gänsicke et al 2006;Hamilton et al 2007;Sion et al 2008;Froning et al 2012), in the case of old novae, A&A 560, A49 (2013) the studies have been fairly preliminary (Gilmozzi et al 1994;Selvelli 2004) or limited to a subset of objects (Szkody et al 1991;Puebla et al 2007Puebla et al , 2011.…”
Section: Introductionmentioning
confidence: 99%
“…In this respect it is worth pointing out that, in contrast to the large number of UV (mostly IUE) and far-UV (mostly FUSE) studies for other classes of CVs (see, for example, Verbunt & Wade 1984;La Dous 1991;Mauche et al 1997;Araujo-Betancor et al 2005;Long 2006; Gänsicke et al 2006;Hamilton et al 2007;Sion et al 2008;Froning et al 2012), in the case of old novae, A&A 560, A49 (2013) the studies have been fairly preliminary (Gilmozzi et al 1994;Selvelli 2004) or limited to a subset of objects (Szkody et al 1991;Puebla et al 2007Puebla et al , 2011.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to this question, Mauche et al (1997) discussed the case of UV line ratios of CVs, which seem to be almost independent of the nature (magnetic or not) of CVs. Okada et al (2008) found from CHANDRA HETG (High Energy Transmission Grating) observations in SS Cyg that the spectrum in quiescence is dominated by H-like K α lines, and is dominated in outburst by He-like lines, which are as intense as H-like lines.…”
Section: Introductionmentioning
confidence: 99%
“…The exception is the large nitrogen to oxygen ratio in GK Per, mirroring the unusual UV line ratios (Mauche et al 1997), and may suggest an abundance anomaly for this system with an evolved secondary (Kraft 1964). As with the cooling flow cases, the He-like triplets again exhibit conversion of the forbidden to intercombination lines, suggesting high electron density and/or a strong, ambient UV radiation field.…”
Section: Photoionized Spectramentioning
confidence: 93%